"First do no harm." A systematic review of the prevalence and management of antipsychotic adverse effects. (April 2015) - Young, Su Ling; Taylor, Mark; Lawrie, Stephen M
Aims: We aim to identify the prevalence and management strategies of nine clinically important categories of antipsychotic adverse effects, namely: extrapyramidal symptoms; sedation; weight gain; type II diabetes; hyperprolactinaemia; metabolic syndrome, dyslipidaemia; sexual dysfunction; and cardiovascular effects. Background: Antipsychotic drugs are widely prescribed for schizophrenia and other mental disorders. The adverse effects of antipsychotics are common, with a potential negative impact on adherence and engagement. Despite this, the scientific study of the prevalence or management of adverse antipsychotic effects is a neglected area. Method: A systematic review was undertaken using pre-defined search criteria and three databases, with hand searching of citations and references. Inclusion was agreed on by two independent researchers after review of abstracts or full text. Quality analysis of included studies was conducted using pre-agreed criteria. Results: In total, 53 studies met inclusion criteria, revealing the following: (1) antipsychotic polypharmacy was associated with increased frequency of adverse effects, and (2) a longer duration of treatment is associated with greater severity (e.g. higher BMI); (3) clozapine was more strongly associated with metabolic disturbance than other antipsychotics in three studies and olanzapine was associated with the most weight gain in three studies; (4) hyperprolactinaemia was more common in women than men, but 50% men noted sexual dysfunction versus 25–50% in women; (5) despite clinical guideline recommendations there is a low rate of baseline testing for lipids and glucose; and (6) seven studies described adverse effect management strategies, but only two examined their efficacy – one found a significant reduction in weight with non-pharmacological group therapy and the other found a significant reduction in dyslipidaemia with statins. Conclusions: Antipsychotic adverse effects are diverse and frequently experienced, but are not often systematically assessed. There is a need for further scientific study concerning the management of these side effects.